PortNet in Morocco : Creating a Strategic Alliance between Port and Foreign Trade Communities for a Competitive Economic Operator - Hafsi, Nadia (International Finance Corporation, Washington, DC, 2017)
In 2008, Morocco’s National Ports Agency launched a project to create a national single-window platform for Morocco’s foreign tr ade. The process was long and difficult, and its success is owing in large part to the leadership and focus demonstrated by PORTNET S.A., the company created in 2012 to be in charge of the project. This SmartLesson describes the steps PORTNET took to forge a strategic alliance between public and private stakeholders in Morocco to achieve a common, mutually beneficial aim: streamline Morocco’s foreign trade procedures and improve its business climate.